ORAL HEALTH AT MIDLIFE AND UNCERTAINTY ABOUT FUTURE DENTAL COVERAGE. (11th November 2018) - Solway, E; Clark, , S; Singer, D; Kirch, M; Malani, P
Abstract: The University of Michigan National Poll on Healthy Aging contracted with GfK to conduct an online survey in April 2017 to a national, probability-based sample of U.S. adults age 50–64 (n=1, 066, completion rate=75%). Sixty percent reported getting regular dental care, but 23% only received care for serious dental problems. Those with dental coverage (72%) were more likely to receive regular preventive care and report good oral health. One-third reported feeling embarrassed about the condition of their teeth; 27% delayed or did not get needed care in the past two years. More than half indicated they do not know how they will get dental insurance when they become eligible for Medicare, and 13% assumed they would have dental coverage through Medicaid or Medicare. Policymakers and clinicians should consider the likelihood and implications of a loss of dental coverage among older adults on oral health and access to care.